BRACHIOPODS OF THE REDEFINED FAMILY TRITOECHIIDAE FROM THE ORDOVICIAN OF KAZAKHSTAN AND SOUTH URALS - Popov L.E.; Vinn O.; Nikitina O.I. (My University, 2001)
The Tritoechiidae are redefined following study of nine species of the genera Tritoechia, Eremotoechia, Martellia Pomatotrema, Protambonites and Korinevskia nov. gen. in Kazakhstanian brachiopod faunas from the upper Tremadoe to lower Caradoc. Six species are new: Tritoechia crassa, T. tokmakensis, Eremotoechia inchoata, E. spissa, Martellia reliqua and Pomatotrema feciinda. In key characters of shell morphology the Tritoechiidae demonstrate close affinity with billingsellids and are therefore reassigned to the superfamily Billingselloidea.
Keywords: Ordovician; Brachiopods; Kazakhstan; South Urals; Paleozoic::Ordovician; Палеозой::Ордовикская